The "Last Word" in Pictures: Enhanced Visual Interpretation of Revelation in Luther's High German Bible (1534). Issue 1 (15th September 2020) - Campbell, W. Gordon
Abstract : For the last twenty-five years of his life, Martin Luther and his associates were active in Bible translation, publishing first the New Testament, from 1522 onwards, and by 1534—at roughly the mid-point of these endeavours—the whole Bible in German. Across this entire period, until his death, Luther continuously offered reader-viewers of the final New Testament book, Revelation, not only verbal commentary—in a preface (1522), or replacement preface with accompanying marginal notes (1530)—but visual exegesis, in the form of successive series of woodcut engravings designed to illustrate the text. A set of images commissioned for Luther's 1534 German Bible was the crowning achievement of this visual interpretation: the 1534 Bible even extended pictorial illustration and adornment to the Gospels and Epistles, as well as Old Testament texts. From the perspective of art history, to regard these acclaimed illustrations as "the last word in pictures" represents no novelty, for the 1534 Luther Bible has long been counted among "the finest things that the art of printing produced in the Reformation period" (Schramm 1923, 22–23; my translation). However, to make the same assertion about the Revelation illustrations specifically, from an explicitly exegetical standpoint—and in English—is new and requires substantiation through supporting evidence. I will provide this through close analysis and evaluation of the interpretative moves that the 1534 images make, in conjunction with Luther's translation and comment, over and against the visual exegesis of their predecessors created, from 1522 onwards, for Luther's German New Testament.